2021
DOI: 10.1210/endocr/bqab138
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Heterogeneity Underlying Adipose Tissue Functions

Abstract: Adipose tissue distribution in the human body is highly heterogeneous, and the relative mass of different depots is differentially associated with metabolic disease risk. Distinct functions of adipose depots are mediated by their content of specialized adipocyte subtypes, best exemplified by thermogenic adipocytes found in specific depots. Single-cell transcriptome profiling has been used to define the cellular composition of many tissues and organs, but the large size, buoyancy and fragility of adipocytes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Consistent with these studies we observed that larger 3T3-L1 adipocytes were less insulin-sensitive than their smaller counterparts. Cultured 3T3-L1 adipocytes therefore exhibit some of the properties associated with cell size that have been identified in primary cells which also exhibit a wide range of size heterogeneity (values between 20 and 300 μm were reported for human adipocytes 25,54,[57][58][59] ).…”
Section: Resultsmentioning
confidence: 79%
“…Consistent with these studies we observed that larger 3T3-L1 adipocytes were less insulin-sensitive than their smaller counterparts. Cultured 3T3-L1 adipocytes therefore exhibit some of the properties associated with cell size that have been identified in primary cells which also exhibit a wide range of size heterogeneity (values between 20 and 300 μm were reported for human adipocytes 25,54,[57][58][59] ).…”
Section: Resultsmentioning
confidence: 79%
“…Based on single-cell or -nucleus sequencing, multiple adipocyte subtypes were recently reported ( 298 , 299 ), opening the avenue to co-cultures with dedicated subpopulations depending on the cell-cell communications to be explored within adipose tissues or with distal organs ( 300 ). In addition, a renewed interest for the ECM: composition, physics and function ( 301 ) paves the way to the culture of fat cells or progenitors with autologous ECM, in vivo or in vitro derived ( 302 ).…”
Section: New Approaches To Specific Analysis Of Tissue Interactionsmentioning
confidence: 99%
“…In order to overcome this, rather than sequencing a whole cell, RNA within nuclei isolated from WAT can be sequenced via single-nuclei RNAseq (snRNAseq) consequently enabling the transcriptomic profiling of single adipocytes. The technical differences, advantages, and limitations of single-cell and snRNAseq for the study of WAT biology have been recently described in detail by Yang Loureiro et al [ 13 ].…”
Section: The Existence Of White Adipocyte Subpopulationsmentioning
confidence: 99%